Do Lasers Have an Adjunctive Role in Initial Non-Surgical Periodontal Therapy? A Systematic Review - Donald Coluzzi; Eugenia Anagnostaki; Valina Mylona; Steven Parker; Edward Lynch (MDPI AG, 2020)
(1) Background: dental lasers have numerous applications for periodontal therapy which include surgical procedures of soft tissue and osseous structures, and non-surgical treatments such as pathogen reduction, removal of surface accretions, and photobiomodulation. The aim of this review was to evaluate the scientific literature to ascertain whether lasers have a beneficial role when used adjunctively in initial non-surgical periodontal therapy. (2) Methods: A PubMed search was performed specifically for randomized clinical trials where a dental laser was used adjunctively for initial periodontal therapy on human patients published from January 2010-April 2020. The first search identified 1294 eligible studies. After additional criteria and filters were applied, 20 manuscripts were included in this review. (3) Results: The chosen manuscripts reported on investigations into initial therapy for patients diagnosed with chronic periodontitis. After periodontal charting, conventional instrumentation such as hand and ultrasonic scaling was performed on all patients in the studies, and then a test group or groups of patients were treated adjunctively with a laser. That adjunctive laser group's periodontal findings showed various degrees of improved health compared to the group treated with only conventional methods. (4) Conclusion: This systematic review found that 70% of the included studies reported significantly better outcomes in certain clinical parameters, but no improvement in others. The remaining 30% of the manuscripts reported no significant difference in any of the measurements. With consideration to correct parametry, lasers have an adjunctive role in initial non-surgical periodontal therapy.